2016
DOI: 10.1108/md-04-2015-0111
|View full text |Cite
|
Sign up to set email alerts
|

How knowledge collecting fosters organizational creativity

Abstract: Structured Abstract:\ud \ud Purpose \ud Based on the interactionist perspective proposed by Woodman, Sawyer, and Griffin (1993), this paper conceives organizational creativity as a complex concept whose investigation requires the understanding of the process, the product, the person, and the situation. Accordingly, this work attempts to enrich the understanding of how organizational creativity can be fostered by offering a framework which combines (inter-)individual-level learning (collecting knowledge from ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 158 publications
(255 reference statements)
1
36
0
1
Order By: Relevance
“…When the new organizational structure is verifi ed to be benefi cial to the organization, the organization needs to store this knowledge and transform it into the organization's path and ability; fi nally, in order to avoid the organization's "path locking" into the "capability trap" organizations need to update their knowledge base from time to time to break path dependence (Rozkwitalska, 2017). Therefore, we deconstructed organizational creativity into four processes: opportunity recognition ability, integration ability, knowledge storage and transformation ability, and breaking path dependence ability (Giustiniano, Lombardi, & Cavaliere, 2016;Friedman & Carmeli, 2018). It also believes that organizational improvisation and experience learning provide the possibility for organizations to cultivate organizational creativity.…”
Section: Organizational Improvisation and Organizational Creativitymentioning
confidence: 99%
See 3 more Smart Citations
“…When the new organizational structure is verifi ed to be benefi cial to the organization, the organization needs to store this knowledge and transform it into the organization's path and ability; fi nally, in order to avoid the organization's "path locking" into the "capability trap" organizations need to update their knowledge base from time to time to break path dependence (Rozkwitalska, 2017). Therefore, we deconstructed organizational creativity into four processes: opportunity recognition ability, integration ability, knowledge storage and transformation ability, and breaking path dependence ability (Giustiniano, Lombardi, & Cavaliere, 2016;Friedman & Carmeli, 2018). It also believes that organizational improvisation and experience learning provide the possibility for organizations to cultivate organizational creativity.…”
Section: Organizational Improvisation and Organizational Creativitymentioning
confidence: 99%
“…However, there are shortcomings in the existing research. On the one hand, the scholars who organize the research genre ignore the knowledge creation as the attribute of organizational ability, and lack attention to the infl uencing factors of organizational creativity construction (Giustiniano, Lombardi, & Cavaliere, 2016;Belschak, Den Hartog, & Kalshoven, 2015). On the other hand, scholars of the existing organization improvisation pay more attention to the connotation and process of improvisation, and whether the organization improvisation is useful in the organizational context and whether it has discussed further.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This process has been considered as a commitment towards organizational innovation and creativity (Cavaliere & Lombardi, 2015;Lilleoere & Hansen, 2011). Giustiniano et al (2016) investigated the way individuals gain knowledge and learn from others and found that knowledge sharing is critical in fostering individual creativity. Thus it could be said that innovation is strongly dependent upon the process by which individuals acquire new knowledge.…”
Section: Mediating Role Of Knowledge Sharingmentioning
confidence: 99%